Surgical and sensory outcomes in patients with intermittent exotropia according to preoperative refractive error - Ahn, Ye Jin (Eye (Lond), 2019)
BACKGROUND/OBJECTIVES: To analyze the surgical and sensory outcomes of intermittent exotropia according to refractive errors and the factors associated with surgical success. SUBJECTS/METHODS: A total of 326 children were divided into three groups according to preoperative refractive error; hyperopic eyes with SE ≥+2D (hyperopic group), eyes with SE between −1D and +2D (emmetropic group), and myopic eyes with SE ≤−1D (myopic group). The surgical outcomes and the sensory outcomes measured by near and distant stereoacuity were compared among the three groups. RESULTS: The surgical success rate in hyperopic group was significantly lower compared to myopic group at last follow-up (P = 0.012). Preoperative near stereopsis was not different among three groups, however, the distance stereopsis was significantly deteriorated in the hyperopic group compared to the other two groups (Titmus; P = 0.168, FD2; P < 0.001, DR; P = 0.048). There was postoperative improvement in both near and distant stereopsis in all three groups (Titmus; P = 0.009, FD2; P = 0.021, DR; P = 0.036) and no significant difference was found in the postoperative distant stereopsis among the three groups. CONCLUSIONS: Preoperative refractive error is a prognostic factor of surgical success in patients with intermittent exotropia. Patients with hyperopia achieved less favorable surgical outcome compared to myopic patients. The preoperative distant stereoacuity was decreased in hyperopic patients compared to myopic patients, which eventually improved after surgery and showed no significant difference at postoperative measurements.